If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5X + -40 = -3X + -26 Reorder the terms: -40 + -5X = -3X + -26 Reorder the terms: -40 + -5X = -26 + -3X Solving -40 + -5X = -26 + -3X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '3X' to each side of the equation. -40 + -5X + 3X = -26 + -3X + 3X Combine like terms: -5X + 3X = -2X -40 + -2X = -26 + -3X + 3X Combine like terms: -3X + 3X = 0 -40 + -2X = -26 + 0 -40 + -2X = -26 Add '40' to each side of the equation. -40 + 40 + -2X = -26 + 40 Combine like terms: -40 + 40 = 0 0 + -2X = -26 + 40 -2X = -26 + 40 Combine like terms: -26 + 40 = 14 -2X = 14 Divide each side by '-2'. X = -7 Simplifying X = -7
| 2x^2-25x+80=0 | | -(3w+4)+5(w-2)-3(6w-8)=1 | | (x+35)=(3x+5) | | 10x^2+9x-117=0 | | 3x+8=4x-10 | | 10x^2+9x-108=0 | | -2x^2+54x=0 | | 6(y-6)/10(y-6) | | H(5x)=3x^2+2 | | 2x^2+52x=0 | | 25x+16y=287.28 | | 2x^2+18x+162=0 | | -2(2x-4x)=6+18 | | 4=2k+22 | | (9y^2-8y+8)-(3y^2-8y+2)= | | -8b+3+6b=3b+8 | | x*1.618=60 | | 5y-8=-28 | | Y^2+18y+69=0 | | 28+9=2n | | 4x/5x-10=35 | | (3.99)2x+19.99y=111.88 | | 2r+12=6 | | -16t^2+25t+10= | | (4x^3-6x+7)=(-19x^3-15x-18) | | -16t^2+25t+8= | | 25x^2+75x-3250=0 | | 18x+94=10x+54 | | x^2-1132x+35200=0 | | u+10=v | | 1/20x=45 | | 8x+41=3x+27 |